(untitled) (Research, Society and Development, 2024)
Introduction: The internet has made technology ubiquitous. Children have increasing access to screens, which can affect their physical, mental, and emotional development. Excessive screen time is associated with sedentary behavior, sleep disorders, and digital dependence. This study aims to identify and critically evaluate publications and scientific evidence related to screen time in childhood and its implications for the individual’s physical and mental health. Methodology: This is an integrative literature review, guided by the question: “What are the implications of screen time in childhood for children’s physical and mental health?”. Data were collected from PubMed, Scielo, and Sciencedirect using the descriptors: "screen time," "childhood," "mental health." Results: The impact of screen time on children’s health was analyzed, gathering 20 articles from various countries. Disadvantages include cognitive delays, concentration and behavior problems, and excess weight. Advantages highlight language stimulation and improvement of behavioral symptoms with educational content. Parental mediation is crucial to minimize negative effects. Discussion: More than 45% of children exceed the screen time recommended by WHO, affecting vocabulary, social interaction, and sleep. However, cognition, language, and fine motor development can benefit from conscious use of technologies. Conclusion: Parental intervention is crucial in determining the impacts on development. Limiting screen time, caregiver attention, socio-educational activities, and social interaction are actions that indicate a beneficial balance. Future studies should clarify the remaining doubts.